2010
DOI: 10.1002/jcb.22504
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Par‐4 sensitizes TRAIL‐induced apoptosis via inactivation of NF‐κB and Akt signaling pathways in renal cancer cells

Abstract: The prostate-apoptosis-response-gene-4 (Par-4) is up-regulated in prostate cells undergoing programmed cell death. Furthermore, Par-4 protein has been shown to function as an effector of cell death in response to various apoptotic stimuli that trigger mitochondria and membrane receptor-mediated cell death pathways. In this study, we investigated how Par-4 modulates TRAIL-mediated apoptosis in TRAILresistant Caki cells. Par-4 overexpressing cells were strikingly sensitive to apoptosis induced by TRAIL compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Par-4 promotes apoptosis in a variety of cancerous cells, but not in normal mature cells. Par-4 kills human carcinoma cells from the prostate (10, 49), kidney (32, 33), pancreas (3), lung (10), cervix (10), endometrium (48), breast (43), and colon (50). It also has activity against melanoma and leukemia (8, 36, 39, 49).…”
Section: Introductionmentioning
confidence: 99%
“…Par-4 promotes apoptosis in a variety of cancerous cells, but not in normal mature cells. Par-4 kills human carcinoma cells from the prostate (10, 49), kidney (32, 33), pancreas (3), lung (10), cervix (10), endometrium (48), breast (43), and colon (50). It also has activity against melanoma and leukemia (8, 36, 39, 49).…”
Section: Introductionmentioning
confidence: 99%
“…Downstream of the DISC, sensitization to TRAIL-induced apoptosis was associated with the deregulation of cell survival proteins including, Bcl-2, Bcl-XL, Mcl-1, HSP27, survivin, IAPs [60, 72-75] or pathways such as AKT and NF-kB [76-79]. …”
Section: Introductionmentioning
confidence: 99%
“…Prostrate apoptosis response-4 (Par-4) is a proapoptotic protein and overexpression of Par-4 sensitizes cancer cell lines and tumor cells to cytotoxicity triggered by anticancer drugs [18]. We therefore examined the relationship between the expression of Par-4 and susceptibility to TAM-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Par-4 is downregulated during tumor recurrence in breast cancer and the downregulation is necessary and sufficient to promote recurrence [17]. Endogenous Par-4 is essential for sensitization of cells to diverse apoptotic stimuli, while the expression of Par-4 induced ectopically or triggered by anticancer drugs can selectively cause apoptosis in cancer cells [18][20]. In addition to its role as an intracellular proapoptotic protein, other studies have demonstrated that secretory or extracellular Par-4 also induces apoptosis in cancer cells and the mechanism involves binding of Par-4 to GRP78 [21].…”
Section: Introductionmentioning
confidence: 99%